Confronting climate gridlock : how diplomacy, technology, and policy can unlock a clean energy future - Cohan, Daniel S. (Yale University Press, 2022)
Atmospheric scientist and environmental engineering professor Daniel Cohan argues that escaping the gravest perils of climate change will first require American diplomacy, technological innovation, and policy to catalyze decarbonization globally. Combining his own expertise alongside insights from more than 100 interviews with diplomats, scholars, and clean-technology pioneers, Cohan identifies flaws in previous efforts to combat climate change. He highlights opportunities for more successful strategies, including international "climate clubs" and accelerated development of clean energy technologies. Grounded in history and emerging scholarship, this book offers a forward-looking vision of solutions to confronting climate gridlock and a clear-eyed recognition of the challenges to enacting them.